2008
DOI: 10.1007/s00027-008-8067-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characterization of chromophoric dissolved organic matter (CDOM) in a fjord (Doubtful Sound, New Zealand)

Abstract: Doubtful Sound, Fiordland National Park, New Zealand has a stable low salinity layer (LSL) at the surface due to the high annual rainfall and an additional freshwater input from the discharge of a hydroelectric power plant. Chromophoric dissolved organic matter (CDOM) distribution dynamics in this LSL were analyzed using Excitation Emission Matrix (EEM) fluorescence and UV/Vis absorption measurements. The levels of CDOM in surface water in Doubtful Sound were much higher than previously reported for coastal zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…The presence of high concentrations of CDOM following the period of heavy rain is likely to derive from the leaching of organic matter from the mature forests and grasslands that cover the adjacent land area, much of which is protected within nature reserves and/or is pristine. Significant CDOM levels have also been observed in New Zealand fjords (Gonsior et al 2008) and Arctic rivers (Retamal et al 2007), with similar characteristics to this region of Chile, but have not been previously reported within the Laguna San Rafael area. Because the estuarine water in this region tends to have high turbidity, either due to high concentrations of suspended fine particulate matter of glacial origin (rock flour) close to Laguna San Rafael or sediment from the Aysé n River, salinity is strongly anticorrelated with turbidity and CDOM in this section.…”
Section: A Spring Campaignsupporting
confidence: 81%
“…The presence of high concentrations of CDOM following the period of heavy rain is likely to derive from the leaching of organic matter from the mature forests and grasslands that cover the adjacent land area, much of which is protected within nature reserves and/or is pristine. Significant CDOM levels have also been observed in New Zealand fjords (Gonsior et al 2008) and Arctic rivers (Retamal et al 2007), with similar characteristics to this region of Chile, but have not been previously reported within the Laguna San Rafael area. Because the estuarine water in this region tends to have high turbidity, either due to high concentrations of suspended fine particulate matter of glacial origin (rock flour) close to Laguna San Rafael or sediment from the Aysé n River, salinity is strongly anticorrelated with turbidity and CDOM in this section.…”
Section: A Spring Campaignsupporting
confidence: 81%
“…The Doubtful Sound contains very high, nearly exclusive terrestrial chromophoric OM character confirmed first by fluorescence spectroscopy . The southwestern slope of the South Island of New Zealand and the northeastern slope of Stewart Island accrue an estimated 400–500 tons of carbon vegetation per hectare with considerable carbon storage values .…”
Section: Resultsmentioning
confidence: 94%
“…The Doubtful Sound contains very high, nearly exclusive terrestrial chromophoric OM character confirmed first by fluorescence spectroscopy. [56] The southwestern slope of the South Island of New Zealand and the northeastern slope of Stewart Island accrue an estimated 400-500 tons of carbon vegetation per hectare with considerable carbon storage values. [57] The lignin-like OM character and recalcitrant nature in both ecosystems could be a result of the higher annual rainfall percentages (>7 m year -1 at Doubtful Sound) and the fjord slope mass-wasting soil and vegetation events that deliver terrestrial OM to the soils and surrounding waters.…”
Section: Effect Of Salinity Gradients On Om From New Zealand Freshwatmentioning
confidence: 99%
“…The chromophores-containing DOM is termed chromophoric dissolved organic matter (CDOM) in the literature (Laurion et al 2000;Gonsior et al 2008). CDOM is sometimes referred to as colored dissolved organic matter (Del Castillo et al 1999;Sulzberger and Durisch-Kaiser 2009).…”
Section: Introductionmentioning
confidence: 99%